Late Stone Age human remains from Ishango (Democratic Republic of Congo): New insights on Late Pleistocene modern human diversity in Africa. Issue 96 (July 2016) - Crevecoeur, I.; Brooks, A.; Ribot, I.; Cornelissen, E.; Semal, P.
Abstract: Although questions of modern human origins and dispersal are subject to intense research within and outside Africa, the processes of modern human diversification during the Late Pleistocene are most often discussed within the context of recent human genetic data. This situation is due largely to the dearth of human fossil remains dating to the final Pleistocene in Africa and their almost total absence from West and Central Africa, thus limiting our perception of modern human diversification within Africa before the Holocene. Here, we present a morphometric comparative analysis of the earliest Late Pleistocene modern human remains from the Central African site of Ishango in the Democratic Republic of Congo. The early Late Stone Age layer (eLSA) of this site, dated to the Last Glacial Maximum (25–20 Ky), contains more than one hundred fragmentary human remains. The exceptional associated archaeological context suggests these remains derived from a community of hunter-fisher-gatherers exhibiting complex social and cognitive behaviors including substantial reliance on aquatic resources, development of fishing technology, possible mathematical notations and repetitive use of space, likely on a seasonal basis. Comparisons with large samples of Late Pleistocene and early Holocene modern human fossils from Africa and Eurasia show that the Ishango human remains exhibit distinctive characteristics and a higher phenotypic diversity in contrast to recent African populations. In many aspects, as is true for the inner ear conformation, these eLSA human remains have more affinities with Middle to early Late Pleistocene fossils worldwide than with extant local African populations. In addition, cross-sectional geometric properties of the long bones are consistent with archaeological evidence suggesting reduced terrestrial mobility resulting from greater investment in and use of aquatic resources. Our results on the Ishango human remains provide insights into past African modern human diversity and adaptation that are consistent with genetic theories about the deep sub-structure of Late Pleistocene African populations and their complex evolutionary history of isolation and diversification.